Efektivitas Micro Teaching dan Pengenalan Lapangan Persekolahan dalam Membangun Kompetensi Profesional: Analisis Kesiapan Mengajar Mahasiswa Calon Guru Administrasi Perkantoran - Juliana Juliana; Alfi Nura (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Teacher readiness is a crucial aspect in preparing prospective educators who are capable of responding to the demands of contemporary education. However, preliminary observations among Office Administration Education students at Universitas Negeri Medan indicated that a considerable proportion of students had not yet demonstrated adequate readiness to enter the teaching profession. Learning experiences obtained through the Micro Teaching course and the Introduction to School Field (PLP) program are considered important factors in strengthening pedagogical competence and professional preparedness. Using a quantitative ex-post facto approach, data were collected from 63 students of the 2022 cohort through a total sampling technique and analyzed using multiple linear regression. The findings revealed that both Micro Teaching and PLP contributed positively and significantly to teacher readiness, both partially and simultaneously. Micro Teaching showed a stronger contribution than PLP in influencing students’ readiness to become teachers. The coefficient of determination value of 86.6% indicates that the two variables jointly explain most of the variation in teacher readiness, while the remaining proportion is influenced by other factors beyond the scope of this research. These findings reinforce the importance of integrating teaching practice and field-based learning experiences in teacher education programs to enhance professional preparedness and support the development of competent future educators.